De la utopía a la presencia (1975-1978) - Giussani, Luigi; Carrón, Julián; Vega, Belé́n de la; Giussani, Luigi (Madrid : Encuentro, 2013)
A collection of speeches and lectures.
Includes bibliographical references and indexes.
Online resource; title from PDF title page (Digitalia, viewed August 25, 2016)
Keywords: Giussani, Luigi -- Interviews; Catholic Church -- Clergy; Religious education; Comunione e liberazione; Electronic books